(3cJGH GdeQV hGdcaGQGJs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3bGd (B: (3MOKfG CHh HcQ YHO Gddg Hf eMeO Hf CHj GdOfjG bGd (B: (3ONdJ Ydi GdfHi Udi Gddg Ydjg hSde hgh eMhe ahVYJ jOi ef ahb GdbWjag ahLOJ MQGQg GdMei s
(3BNQgG (B:s
(3hCeG eG cGf jLH Cf jJbGdfG efc hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs